Upaya Peningkatan Keaktifan Siswa Melalui Pembelajaran Cerita Jātaka di Sekolah Minggu Buddhis Viriya Dhamma Kabupaten Semarang - Ismadi Ismadi; Sukodoyo Sukodoyo; Widiyono Widiyono (Jurnal Maitreyawira, 2022)
ABSTRACT This study aims to determine the success of increasing student activity at SMB Viriya Dhamma through the Jātaka story. This research is a Classroom Action Research (CAR) using the Kemmis & McTaggart model. The research was carried out at SMB Viriya Dhamma Wates, Semarang Regency. The research subjects are nine students and two teachers. The data collection techniques and instruments used were observation, interviews, and documentation. The instrument used was student and teacher observation sheets. Data analysis in this study used descriptive quantitative analysis and descriptive qualitative analysis. The results showed that the Jātaka story was very effective in increasing the learning activity of SMB Viriya Dhamma students. The Jātaka stories told in this study are the Devadhamma Jātaka, Gāmani Jātaka, and Nalapāna Jātaka. Viriya Dhamma SMB students' active learning can be seen from the results of research which shows an increase in SMB students' learning activities from Pre-Cycle to Cycle II. In the Pre-Cycle, the learning activity of SMB students was 150 and Cycle I increased to 194. In Cycle I, the learning activity of SMB students from 67.36% increased by 94.44% in Cycle II. In Cycle I it got a value of 194 and in Cycle II it increased by 272. The success of the actions taken in this study is influenced by several factors, including the condition of students, attendance, teachers, peers